EXPERIMENTAL ANALYSIS AND INNOVATION STRATEGIES FOR BIFACIAL PHOTOVOLTAIC MODULES (Uzbek Scholar Journal, 2026)
As the third largest renewable energy source at present, solar photovoltaic (PV) technology has become a significant player in the global energy industry [1]. New solar module designs are emerging as photovoltaic technology advances. Bifacial PV modules are one of them that have attracted much interest in recent times [2,3]. Bifacial designs have the unique feature of generating power from both the front and back surfaces, which can result in higher power generation than traditional monofacial modules. The amount of irradiation received at the back surface is the main factor affecting the performance of bifacial modules. Direct irradiance, ground reflected irradiance, structure reflected irradiance, and diffuse sky irradiance make up the total irradiance at the back side of the module [4].